DIFFERENT CONCENTRATIONS OF SIJUNZI DECOCTION INHIBIT PROLIFERATION AND INDUCE APOPTOSIS OF HUMAN GASTRIC CANCER SGC-7901 SIDE POPULATION - Qian, Jun; Li, Jing; Jia, Jianguang; Jin, Xin; Yu, Dajun; Guo, Chenxu; Xie, Bo; Qian, Liyu (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: SD is a traditional Chinese medicine which composed of Ginseng, Atractylodes, Poria and Licorice. It is one of the commonly used Chinese traditional medicines that showed anti-gastric cancer activity in clinical studies. Previous evidence demonstrated SD parties (Ginseng, Atractylodes, Poria, Licorice) can inhibit proliferation and induced apoptosis for gastric cancer cell. In order to further investigate the anticancer effect of SD in gastric cancer, we observed the effects of different concentrations of SD on proliferation and apoptosis of SP of human gastric cancer SGC-7901. Materials and Methods: 1. SGC-7901 side population cells were sorted through flow cytometry. 2. To detect the changes of proliferation of SP and NSP before and after the intervention of serum containing different concentrations of SD using cck-8 method. 3. To detect the changes of cell cycle and apoptosis of SP and NSP before and after the intervention of serum containing different concentrations of SD through flow cytometry. 4. To detect the effects of serum containing different concentrations of SD on apoptosis-related proteins Bax and Bcl-2 of SP and NSP before and after the intervention by western-blot. Results: It was found that different concentrations of SD serum treatments inhibited cell proliferation in a time-dependent and concentration-dependent manner. Compared with the control group (normal saline treatment), there were increase in G1/G0 phase population of SP and NSP, and decrease in G2/M and S phase population (P<0.05). Meanwhile, we found G1/G0 arrest induced by different concentrations of SD serum which was followed by apoptosis in a time-dependent and concentration-dependent manner. The apoptosis rate of drug serum treatment group was higher than the control group (P<0.05), the apoptosis rate of 48 h treatment was higher than 24 h treatment (P<0.05), and as the drug serum concentration increases, apoptosis rate is higher and higher (P<0.05). The expression of Bax protein of SP and NSP was higher than the control group in a time-dependent and concentration dependent manner. The expression of Bcl-2 protein of SP and NSP was lower than the control group in a time-dependent and concentration- dependent manner.Conclusion: With the increase of SD serum concentrations , SD can gradually inhibit the proliferation of SP of SGC-7901 cell lines through G1/G0 phase arrest and followed by apoptosis which involves the up-regulation of Bax and the down-regulation of Bcl-2.